Dampak Realokasi Dana Desa Selama Pandemi Covid-19 Terhadap Kinerja Desa : Analisis Data Kabupaten - Rizki Rizki Harismawan Januarsyah (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2025)
During the COVID-19 pandemic, the government enacted Presidential Regulation No. 104 of 2021 by reallocating the Village Fund for COVID-19 response. This study aims to identify whether the reallocation of the Village Fund contributes to a decrease in the effect of the Village Fund on village performance. This study also relates whether the severity of COVID-19 has an impact on the decline in village performance. The data used is annual panel data of 416 districts in the period 2018 - 2021. Using the Panel Least Squares (PLS) method, this study revealed that the reallocation of village funds led to a decrease in the influence of the Village Fund on village performance.